2011
DOI: 10.1007/s10120-011-0015-7
|View full text |Cite
|
Sign up to set email alerts
|

Survival benefit of gastrectomy ± metastasectomy in patients with metastatic gastric cancer receiving chemotherapy

Abstract: Background This study was performed to investigate the role of surgery in patients with gastric cancer and distant metastases who had received systemic chemotherapy. Methods Patients with newly diagnosed gastric cancer and synchronous distant metastases who had received chemotherapy (n = 274) were categorized into 3 groups according to the surgical treatment rendered: complete gross resection of both primary and metastatic sites (group A; n = 42); debulking gastrectomy (group B; n = 47); and chemotherapy witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 25 publications
2
65
0
Order By: Relevance
“…In order to improve survival, there is a need to investigate the optimal management of Krukenberg tumors. For patients with gastric cancer, a Korean study suggested that debulking or gastrectomy plus metastasectomy may achieve survival benefits for patients with distant metastases who were receiving systemic chemotherapy (23). In our study, over two-thirds of the patients received chemotherapy.…”
Section: Univariate Analysis Multivariate Analysis ------------------mentioning
confidence: 64%
“…In order to improve survival, there is a need to investigate the optimal management of Krukenberg tumors. For patients with gastric cancer, a Korean study suggested that debulking or gastrectomy plus metastasectomy may achieve survival benefits for patients with distant metastases who were receiving systemic chemotherapy (23). In our study, over two-thirds of the patients received chemotherapy.…”
Section: Univariate Analysis Multivariate Analysis ------------------mentioning
confidence: 64%
“…Even in large volume centers, gastrectomy for metastatic gastric cancer has been reported to be associated with high rates of morbidity (>50%) and mortality (6–12%) [7,23]. Some recent studies [24,25] reported acceptable postoperative morbidity and mortality rates. In this study, severe postoperative morbidity was uncommon and there were no surgery-related perioperative deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of metastasectomy is well established for colorectal cancer and sarcoma, there is still controversy regarding the usefulness of surgery targeting metastatic lesions in patients with gastric cancer, who have a reported median survival time of 11.2–31.0 months [24,26]. Some non-randomized comparative analyses suggested that aggressive surgical treatment of patients with metastatic gastric cancer prolongs survival.…”
Section: Discussionmentioning
confidence: 99%
“…Peritoneal carcinomatosis can be difficult to evaluate radiologically [8]. However it is recommended to use the Sugarbaker peritoneal cancer index (PCI) which describes 4 levels (Cotte).…”
Section: Metastatic Gastric Cancermentioning
confidence: 99%